The connecting brain in context: How adolescent plasticity supports learning and development - Amanda E. Baker; Adriana Galván; Andrew J. Fuligni (Developmental Cognitive Neuroscience)
Puberty initiates significant neurobiological changes that amplify adolescents’ responsiveness to their environment, facilitating neural adaptation through processes like synaptic pruning, myelination, and neuronal reorganization. This heightened neuroplasticity, combined with their burgeoning social curiosity and appetite for risk, propels adolescents to explore diverse new environments and forge social bonds. Such exploration can accelerate experiential learning and the formation of social networks as adolescents prepare for adult independence. This review examines the complex interplay between adolescent neuroplasticity, environmental influences, and learning processes, synthesizing findings from recent studies that illustrate how factors such as social interactions, school environments, and neighborhood contexts influence both the transient activation and enduring organization of the developing brain. We advocate for incorporating social interaction into adolescent-tailored interventions, leveraging their social plasticity to optimize learning and development during this critical phase. Going forward, we discuss the importance of longitudinal studies that employ multimodal approaches to characterize the dynamic interactions between development and environment, highlighting recent advancements in quantifying environmental impacts in studies of developmental neuroscience. Ultimately, this paper provides an updated synopsis of adolescent neuroplasticity and the environment, underscoring the potential for environmental enrichment programs to support healthy brain development and resilience at this critical development stage.